The impact of final exams on student stress levels and sleep quality - Andika, Ari; Aryani, Atik; Sutrisno (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Scientific papers (STPs) are written presentations of case studies that discuss a problem in a specific scientific field using the principles applicable to the field. Obstacles in the process of writing scientific papers make students susceptible to stress, which impacts their sleep quality. Poor sleep quality can lead to students being unable to focus, becoming distracted, and increasing negative thoughts. Purpose: To determine the relationship between stress levels and sleep quality among final-year nursing students preparing STPs at Poltekkes Karya Husada Yogyakarta in 2025. Method: This study used a descriptive correlational design with a cross-sectional study design. A sample of 96 students was drawn using simple random sampling. The research instruments used a stress level questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results were analyzed using a gamma test. Results: 43 students (44.8%) experienced moderate stress and 30 students (31.3%) experienced mild stress. Sleep quality: 78 respondents (81.3%) reported poor sleep quality, while 18 respondents (18.8%) reported good sleep quality. The Gamma test yielded a p-value of 0.001 < 0.005, with a correlation coefficient of 0.441. Conclusion: There is a significant relationship between stress levels and sleep quality in final-year nursing students. Keywords: Stress; Sleep Quality; Students.